Inward - Punzalan, Martinez Danielle (Nanyang Technological University, 2024)
The purpose of "Inward" is to further push the boundaries of storytelling by utilizing songwriting and motion capture to encapsulate emotions and feelings through dance and visual effects. In collaboration with local artists, Danielle Martinez and Megan Tang employed XSens, Unreal Engine, and Houdini to create a 3D animated music video exploring the 5 stages of grief. Danielle's roles encompassed Director, Editor, Lighting Artist, Environment Artist and Motion Capture Animator, while Megan focused on taking lead for both Character Design and Environment Artist, together with creating 3D simulations. The project culminated in the original song "Let Go," complementing the narrative as the music video depicts a girl's emotional journey through a symbolic maze. This interdisciplinary approach, coupled with collaboration with musicians, contributes to the project's originality and value, offering a novel perspective on multimedia storytelling and emotional expression.